Impact of Skype in Teaching Listening Comprehension - rugaiyah rugaiyah (J-SHMIC : Journal of English for Academic, 2017)
This paper shows the ELT educational trend has recently been gaining in significance in education systems throughout the world. English Language Teaching (ELT) has tremendously changed over the last one decade. Technology in education has become the buzz word in every educational environment. Technologies like internet, skype, you tobe, tweeter. Mobile phones and many more have added not only stimulus but also learners’ engagement and true interactivity with the classroom. One widespread method online teaching involves the use of skype, a powerful application that provides users with free internet voice chatting service.Skype can be a wonderful opportunity to expand learning situations through voice, text and video sessions.This paper is focused on analyzing the impact of Skype on students’ listening comprehension for a group of 21 students of fourth semester of FKIP UIR Pekanbaru in academic year 2014/2015. This study used classroom action research. The instruments of this research were tests, observation, interview, and field notes. The data collection was accomplished by means of students’ reflection questionnaires posterior to the Skype, field notes of the investigator, and comprehension tests. The finding shows that the use of Skype can improve students’ listening comprehension. It can be seen from the increasing of mean score of the tests.The results of the first cycle of 69.52 learning increased to 71.43 in the second cycle.